REGULAR OBSERVATION OF CHILDREN WITH BRONCHIAL ASTHMA BY ALLERGOLOGIST AND ITS INFLUENCE ON CLINICAL AND FUNCTIONAL PARAMETERS OF THE DISEASE AND CONSUMPTION OF HEALTHCARE RESOURCES - I.P. Artyukhov; N.A. Il'enkova; A.V. Shul'min; L.V. Stepanova (Вопросы современной педиатрии, 2011)
In real practice, treatment of patients with bronchial asthma (BA) is accompanied by unreasonable increase of healthcare resources consumption because of unplanned visits to the doctor due to health worsening, hospital treatment of exacerbations and emergency calls. Objective: to evaluate an effectiveness of children’s with bronchial asthma observations by allergologist. Methods: the dynamics of clinical and functional signs and frequency of emergency claims was analyzed in 115 children with BA who were observed by allergologist once in 3 months during one year. Results: in 3 months of regular observation by allergologist the number of children with day and night symptoms of BA and patients with daily rescue use of short-acting 2-agonists decreased, there were fewer children with limitations of physical activity. The number of patients with normal FEV1 increased in 6 months. Regular observation with allergologist resulted in reduction of number of patients with exacerbations and hospitalizations, shortening of acute period of BA and hospital stay, decreasing of emergency claims rate compared to those who were observed by GPs. Conclusion: regular observation by allergologist once in 3 months results in stabilization of clinical and functional state in patients with BA and decreases the consumption of emergency care resources. Key words: children, bronchial asthma, allergologist, clinical and functional state, healthcare resources. (Voprosy sovremennoi pediatrii — Current Pediatrics. 2011; 10 (3): 55–59)